Союз промышленности и высшей школы в решении инновационных задач - Бобкова, Е.А.; Щукина, Т.Н. (My University, 2016)
This article discusses issues related to the main areas of higher education in solving the problems of innovative industries. It attaches great importance to the establishment of national innovation systems , linking science and business .
Keywords: innovative activity; higher education and industry